Induction of human T-cell tolerance to porcine xenoantigens through mixed hematopoietic chimerism - Lan, Ping; Wang, Lan; Diouf, Bintou; Eguchi, Hiroshi; Su, Hui; Bronson, Roderick; Sachs, David H.; Sykes, Megan; Yang, Yong-Guang (Blood, 2004)
Xenotransplantation from pigs could provide a potential solution to the severe shortage of allogeneic donor organs. Because xenogeneic tissues are subject to vigorous immune rejection, tolerance induction is likely to be essential to the success of clinical xenotransplantation. Here we explore the possibility of inducing human T-cell tolerance to porcine xenografts through mixed chimerism. We previously showed that NOD/SCID-Tg mice expressing porcine cytokine transgenes permit the induction of durable porcine hematopoietic chimerism. In this study we achieved human T-cell development in these mice by engrafting human fetal thymus/liver tissues. In porcine hematopoietic chimeras, human thymus grafts were populated with porcine class IIhigh cells in addition to human cells, and human T cells were tolerant of the porcine hematopoietic donor as measured by mixed lymphocyte reaction assay and skin grafting. This study proves the principle that porcine chimerism induces tolerance of xenoreactive human T cells.